Cartel Stability Under Vertical Differentiation and Convex costs: Bertrand vs Cournot - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
The issue of a cartel stability is investigated in a vertical differentiation framework with convex variable production costs. The behaviour of firms' critical discount factors as the curvature of the cost function varies is analysed, considering either the noncooperative or cooperative qualities, and either price or quantity behaviour. It emerges that, if firms aim at stabilizing the cartel, they are better off paying à la Counot and prefer not to choose the monopoly qualities.
Keywords: 330